Diving into the bitstream information technology meets society in a digital world - Dumas, M. Barry (New York : Routledge, 2013)
"Nationwide, and indeed worldwide, there has been a growing awareness of the importance of access to information. Accordingly, information technology (IT), broadly defined and its role beyond the internal workings of businesses has leapt into the social consciousness. Diving into the Bitstream distinguishes itself by weaving together the concepts and conditions of IT. What distinguishes these trends is their focus on the impacts of IT on societies, and the responsibilities of IT's creators and users. The author pulls together important, often complex issues in the relationships among information, information technologies, and societal constructs. The text explores a synopsis of these issues that are foundations for further consideration. "--
ch. 1. What's it all about? -- ch. 2. Information to suit : as you like it -- ch.3. Connections : the Internet, the Web, and the others -- ch. 4. That is to say : free expression and privacy -- ch. 5. What's mine is whose? : intellectual property -- ch. 6. You, me, and everyone else : alone together and vice versa -- ch. 7. Attacks, bit by bit : from nuisance to cyber warfare -- ch. 8. Mind and machine : artificial intelligence -- ch. 9. We are what we do : ethics and responsibilities -- ch. 10. The future lies ahead : we're off to see ...
Includes bibliographical references (p. [258]-260) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Information technology -- Social aspects; Information society; Electronic books